Visual Behavior Modeling of Hazard Identification Assessment From Eye-Tracking Data - da Silva, Abner Cardoso; Raposo, Alberto Barbosa; Franco, Cesar Augusto Sierra (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
The easier access to virtual reality head-mounted displays have assisted the use of this technology on research. In parallel, the integration of those devices with eye-trackers enabled new perspectives of visual attention analysis in virtual environments. Different research and application fields found in such technologies a viable way to train and assess individuals by reproducing, with low cost, situations that are not so easily recreated in real life. In this context, our proposal aims to develop a model to measure characteristics of safety professional’s gaze behavior during the hazard detection process.